THE IDENTIFICATION OF CHROMOSOMAL POLYMORPHISM IN ONE BREED OF IRAQI SHEEP - A. Yasseen, A.; T. Ridha-Albarzanchi, M.; A.M. Alanssari , S.A.M. Alanssari; G.Hussain , S. (The Iraqi Journal of Veterinary Medicine, 1989)
A chromosomal analysis of three breeds of Iraqi sheep (Karadi Arabi and Awassi) has been performed on peripheral lymphocytes. The modal chromosome number of all the three breeds was found to be (2n=54XX/54XY) for femal and male respectively. The karyotype of Awassi differ from the rest of the domestic sheep (Ovis aries) by the presence of a pericentric inversion on one copy of chromosome number 3. Basal minimal medium supplemented with foetal bovine serum was the most suitable culture medium to produce sufficient mitotic cells for chromosomal analysis.